Observing the angle of attack of the tip-path plane from rotor blade measurements - Trainelli, L.; Riboldi, C.E.D.; Bucari, M. (My University, 2015)
A recurring problem in helicopters is the difficulty to accurately measure the angle of attack of the airframe and tip-path plane with respect to the slipstream. Differently from fixed wing aircraft, it is hard to find a spot on the airframe of a helicopter where the velocity vector of the stream is not polluted by a very relevant downwash component due to the deflecting action of the main rotor on the air stream. Furthermore, the geometrical definition of the tip-path plane calls for the knowledge of the attitude of the blades with respect to a plane normal to the main rotor mast. This attitude is related to the flap motion of the blades, which to this time cannot be measured effectively through a direct measurement method. Building on the experience and research results of the MANOEUVRES project, which is aimed at developing a novel sensor for the flap motion of the blades, making possible monitoring the noise intensity emitted by the helicopter during approach maneuvers, this paper presents a possible way to estimate the angle of attack of the tip-path plane starting from a basic set of measurements including those related to the flapping angle of the blades. The knowledge of the flap motion of the blades allows to observe also other flight mechanics performance parameters, like the thrust force coefficient, without the need for further sensor information. Support for the feasibility of the proposed observer comes from the well known equations for the flapping blade. The presented results assessing the quality of the synthesized observer and its ability to work under both design and off-design conditions have been obtained working on the virtual model of an existing machine.
Keywords: Green Rotorcraft